2020
DOI: 10.48550/arxiv.2009.06683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Nickel Mass Distribution of Stripped-Envelope Supernovae: Implications for Additional Power Sources

Niloufar Afsariardchi,
Maria R. Drout,
David Khatami
et al.

Abstract: We perform a systematic study of the 56 Ni mass (M Ni ) of 27 stripped envelope supernovae (SESNe) with both well-constrained rise times and late-time coverage (>60 days) by modeling their light-curve tails. Based on this sample, we find that using "Arnett's rule" with observed peak times (t p ) and luminosities (L p ) will overestimate M Ni for SESN by a factor of ∼2. Recently, Khatami & Kasen (2019) presented a new analytic model relating t p and L p of a radioactive-powered SN to its M Ni that addresses se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…For stripped-envelope SNe such as the one considered here, this can have a large effect on the reported mass estimates (Khatami & Kasen 2019). We adopt the value of 𝛽 = 0.9 that has been empirically calibrated from a sample of well-studied SNe Ic (Afsariardchi et al 2020).…”
Section: Explosion Kinetics From Bolometric Fittingmentioning
confidence: 99%
“…For stripped-envelope SNe such as the one considered here, this can have a large effect on the reported mass estimates (Khatami & Kasen 2019). We adopt the value of 𝛽 = 0.9 that has been empirically calibrated from a sample of well-studied SNe Ic (Afsariardchi et al 2020).…”
Section: Explosion Kinetics From Bolometric Fittingmentioning
confidence: 99%
“…From these analyses, we conclude that our results in section 6 are robust to the different methods of deriving 56 Ni mass. It is true that several works model the incomplete γ-ray trapping when using the tail luminosity of SESNe (Afsariardchi et al 2020;Sharon & Kushnir 2020). Since the 56 Ni masses derived from such methods typically lie between 'Tail mass' and 'Arnett mass' (Sharon & Kushnir 2020), the effect of using such methods on the mock observation is covered by our discussion on the two cases above (i.e., 'Arnett mass' and 'Tail mass').…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the 'Arnett-rule', which has been widely used for SESNe have been claimed to overestimate the 56 Ni mass (Dessart et al 2015(Dessart et al , 2016Khatami & Kasen 2019). However, several works have concluded that even by taking into account the different methods to derive the 56 Ni mass and various observational errors, a difference in 56 Ni masses between SNeII and SESNe remains (Afsariardchi et al 2020;Meza & Anderson 2020;Sharon & Kushnir 2020). Meza & Anderson (2020) further noted the possibility that SESNe with a small amount of 56 Ni might have been missed by the existing surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 also shows a few magnetar rotation period estimates obtained by modeling "normal" type Ib SNe, which likely arise from He stars formed in binaries (e.g., Zapartas et al 2021). Afsariardchi et al (2020) provided estimates for many events by assuming a typical ejecta mass of either 2 M or 5 M . They found magnetar rotation periods very similar to those predicted by our models were consistent with helping to power the events they analyzed.…”
Section: Comparison With Observed Supernovaementioning
confidence: 99%